The Impact of Innovative City Pilot Policy on Urban Land Green Use Efficiency: A Quasi-Natural Experiment from China - Hengzhou Xu; Zhongyue Li; Luyu Guo; Yingfei Liu (Land)
China’s rapid urbanization has spurred significant economic growth, but it has also given rise to challenges such as urban sprawl, ecological degradation, and inefficient land use—issues that impede progress toward green and sustainable development. Land is the spatial foundation for green development, and promoting its green utilization is essential for advancing the high-quality development of urban spaces. As a concrete implementation of the innovation-driven development strategy, the National Innovative City Pilot Policy (NICPP) serves as a crucial driver in fostering high-quality development. In this context, the NICPP and green land use can be seen as two complementary components of achieving high-quality development. This study uses panel data from 266 cities across China and applies a difference-in-differences (DID) model to evaluate the effect of the NICPP on urban land green use efficiency (ULGUE), exploring the underlying mechanisms through the lenses of industrial structure and technological innovation. The results indicate that the NICPP significantly and robustly enhances ULGUE. The effect varies geographically and by city type, with the most pronounced benefits observed in eastern cities, non-resource-based cities, and non-old industrial base cities. Additionally, the NICPP contributes to improved comprehensive output benefits during land use activities and reduced pollutant emissions by optimizing industrial structures and enhancing technological innovation capacity, thereby promoting ULGUE. Therefore, in the future, the focus should be on integrating innovation with strategic policies. These findings carry profound implications for urban development in China and provide important lessons for promoting sustainable urban growth on a global scale.